The Humour of Sociolects and Idiolects among Heterogeneous Audiences in Contemporary Nigerian Stand-up Comedies - Idowu James Adekunle (RIRAI Publisher, 2023)
Stand-up comedy, a trans-tribal and gender-equality profession among talented Nigerian youths, is posed with different linguistic barriers in communication exchange between tribal performers and their heterogeneous audience and between intertribal performers and homogeneous audiences because of cultural differences. In Southwest Nigeria, the Yoruba call it